Comparison of angular and linear measurements of soft tissue profile between cephalograms and photograph in subjects with class I and II malocclusion in North Indian population- A comparative study - Dayal, Shubham; Saxena, Himanshu; Kulshrestha, Rohit; Agarwal, Kirti; Rai, Divya; Hawaldar, Chinmaya (Journal of Orofacial Research, 2019)
Aim: The aim of the present study was to compare angular and linear measurements of soft tissue profile between cephalograms and photograph in subjects with Class I and Class II malocclusion. Method: Samples consist of digital lateral cephalograms and profile photograph of 100 subjects (50 Class I and 50 Class II, 25 males and 25 females in each group) between age ranges of 18 to 35 years (mean age 22+/- 2.32). All records were taken in natural head position, centric occlusion and lips in relaxed position. Intra-class correlation coefficients (ICCs) were calculated from repeated photographic measurements to evaluate method reliability. Seven angular and fourteen linear parameters were measured for soft tissue analysis on both lateral cephalogram and photographs. Student’s t-test was done for making adequate comparison. Results: The reliability of the photographic technique was found satisfactory and no statistical difference in angular as well as linear parameters was found for soft tissue profile on both photographs &cephalogramsrespectively. Conclusion: Photographs can be used as an alternative for cephalograms in epidemiologically large-scale studies, where there is a need for cost effective, non-invasive techniques.